Analysis of intrinsic apoptosis in endothelial cells exposed to calcium phosphate bions - V. E. Markova; D. K. Shishkova; A. G. Kutikhin (Фундаментальная и клиническая медицина, 2020)
Aim. To study intrinsic apoptosis in primary arterial endothelial cells treated with calcium phosphate bions (CPB). Materials and Methods. Primary human coronary artery endothelial cells were exposed to spherical or needle-shaped CPB during 4 hours with the subsequent extraction of total protein and subcellular fractionation to separate mitochondrial and cytosolic protein. We then performed Western blotting to measure the relative levels of a mitochondrial marker porin, cytosolic marker glyceraldehyde 3-phosphate dehydrogenase and intrinsic apoptosis proteins cytochrome c and HtrA2/Omi in mitochondria and cytosol in addition to the levels of total and cleaved caspases-9 and caspases-3 in the total protein collected from three independent experiments. Results. Translocation of cytochrome c and HtrA2/Omi was not a mandatory consequence of CPB exposure. Relative levels of the measured proteins differed according to the particle shape. Out of three experiments, only one showed a significant increase in cleaved caspase-9 and caspase-3 in CPB-treated as compared with the mock-treated cells. In other experiments, cleaved caspases did not show a consistent elevation. The levels of total and cleaved caspase-9 and caspases-3 were concordant testifying to the direct correlation between them. Conclusion. As mechanisms of CPB-induced endothelial toxicity are poorly defined, they require further investigation employing optimized methods.